Association of Epstein-Barr Virus (EBV) and Human Endogenous Retroviruses (HERV) with Multiple Sclerosis in Northwest of Iran - Sara Mafi; Dariush Savadi Oskoee; Hossein Bannazadeh Baghi; Arezou Azadi; Mahin Ahangar Oskouee (Hindawi Limited, 2023)
Background and Objective. Multiple sclerosis (MS) is a progressive disease of the nervous system that leads to demyelination of the nerves and is more common in young adults, especially women. Environmental factors that trigger MS pathogeneses are genetic susceptibility and viral infections. The viral infections are considered to be of particular relevance. Along with viruses belonging to the Herpesviridae family such as varicella zoster virus (VZV), human herpes virus-6 (HHV-6), and particularly Epstein-Barr virus (EBV), the expression of the env gene of human endogenous retrovirus (HERV-W) like MSRV is expected to be one of the risk factors for bringing up MS and disease progression. The present study aimed to investigate the correlation between EBV infection and HERV-W env in a case group (MS patients) and a control group (healthy individuals). Materials and Methods. 130 subjects were enrolled in a case-control study at two tertiary university hospitals from Tabriz (Imam and Razi), Iran. Of these, 65 subjects were MS patients serving as the case group, and 65 subjects were healthy individuals serving as the control group. After DNA extraction from all samples, the EBER region of EBV genome was used as the primer for the detection of EBV. RNA was extracted from PBMCs, and cDNA synthesis was performed by using Sina Gene kit. Subsequently, each sample was analysed by RT-PCR with two sets of primers to detect specifically multiple sclerosis retroviruses (MSRV) env, and RT-PCR was repeated for each HERV-W env. Positive sample was used in order to confirm the result. Results. In the case group, 19 (29.2%) patients were male and 46 (70.8%) patients were female. Nevertheless, in the control group, 21 (32.3%) subjects were male and 44 (67.7%) subjects were female. No significant difference was found between groups in gender (p = 0.70). The mean range in control and case groups was 33/38 ± 9/85 and 33.18 ± 8.65, respectively. No significant difference was found between groups in age (p = 0.902). 4 (6.2%) patients in case groups were found to be positive for EBV DNA (p = 0.119). Expression of the env gene of HERVs was observed in 10 (15.38%) and two (3.07%) specimens in the case and control groups (p = 0.030), separately. A comparison of the prevalence of the HERV ENV genome between the two study groups showed a significant difference (p = 0.005). Conclusion. The results of this study failed to show any difference between MS patients and healthy controls in the rate of EBV infection. It can be concluded that the expression of HERV-W/env genes may be involved in the development of MS in these patients.